Addition of Hydrogen Peroxide to Soy Lecithin and Analysis of Possible Changes in its Physical-Chemical Patterns (Research, Society and Development, 2022)
Among the various products from the industrialization of soybeans, lecithin is one of the industrial components commonly added to foods. This article has the premise of evaluating, theoretically, what the lecithin production industry must guarantee in relation to its physical-chemical and microbiological parameters, guaranteeing its customers that the final product has an adequate quality standard. As a second theme, the objective is to analyze the effect of the addition of different concentrations of hydrogen peroxide (PH) (1 to 10%) analyzing its impact on the physicochemical quality standards of soy lecithin. The analyzes performed were to determine viscosity, acidity, peroxides, insoluble in hexen, insoluble in acetone, moisture and color. With the result of the addition of PH, it was observed that as for the insolubility, there is a difference for acetone and hexane, and the insolubility in acetone was not influenced by the addition of PH, while for hexane, between 1 and 2% there was no increase in its insolubility. , however from 3% there was an increase, but it becomes stable up to 10%. Regarding acidity, it was sensitive to the addition of PH, with a gradual decrease according to the addition of this peroxide. For viscosity and color analyses, there was no significant difference. The impact is the humidity, being more sensitive, being observed a gradual increase according to the addition of PH. It is concluded that the addition of PH interferes with the quality of soy lecithin, mainly in relation to its acidity and moisture, which may compromise quality.